The Welfare of Pregnant and Birthing Women as a Concern for Male and Female Rulers: A Case Study - Aikin, Judith Popovich (The sixteenth century journal, 2004)
Members of the ruling family of the twin principalities of Schwarzburg in seventeenth-century Germany took a variety of actions to professionalize midwifery and to improve the situation for birthing women and their infants. At least four different countesses of Schwarzburg were involved in helping birthing women by participating in the selection of midwives, manufacturing and distributing pharmaceutical products, and sponsoring the publication of medical and devotional manuals for the use of midwives and the women they served. The most active of these countesses also authored the song and prayer texts contained in a devotional handbook for pregnant and birthing women and midwives, which she distributed to households in the principality. One male ruler, perhaps in partnership with the countess, acted during the same period to improve obstetric care by spearheading the creation and establishment of an official midwife ordinance and by sponsoring publication and distribution of an obstetric handbook for midwives.